Changes in swimmer's performance due to non-steroidal anti-inflammatory (NSAID's) analgesy - Ramos da Silva, E.; Martins Kruel, L. F.; Ortiz Ferreira, A.; Korzenowski, A.; Pereira, T.; Dossena Henkin, S. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Since at least 100 years, NSAID`s are taken abusively without medical prescription by non athletes(6,11) and athletes( 1,2,4). In the beginning, Aspirin R represented this drugs, then replaced for Ibuprofen (Ibu) and Naproxen, that are more efficient antinflamatories, analgesics and antipyretics(5). This drugs block prostaglandins production responsable for nociceptive hiperalgesy by inhibiting constitutive and inductive cicloxigenase (COX1 e COX2). Nowadays, COXIB`s selectively block the COX2 reducing the undesired effects without altering the effectiveness of the drug(3). Its applicability in exercise has been investigated in post effort situations in the treatment of Delayed Onset Muscle and soreness, however there are few studies about acute analgesy(8,10) in the performance of endurance sports(7). Thus, the purpose of this study was to verify the interference of prophylactic usage of Ibuprofen in the performance of long distance swimmers. In a short course pool, 9 elite level male swimmers, aged 17,7+2,6 years, body mass 74,3+5,3kg, height 180,2+7,5cm, body fat 6,4+2,6% and time in sport 6,3+2,1 years, underwent to 2 maximal testes of 1500 m with 5 days interval. Subjects took 1,2gr of Ibu 1 or 1,2gr of placebo (pla) (aleatory and double-blind) 1 hour before they entered in the pool. Training and food intake were established before the test. Total time of exercise in each situation was registered and blood lactate (mmol) pre exercise (1h) and pos exercise (1min) were collected. [delta = pos - pre]. One way analyses of variance (ANOVA) was used to compare treatments with p<0.05. Significative difference (p=0.02) was observed in the total time of 2 situations (pla=19:10+00:50 e Ibu=18:48+00:40), and in lactate concentration (pla=5,1+2,2 e Ibu=6,3+2,2. p=0.04). The results indicate that the drug increased the speed of the swimmers (and energetic demand) explaining the higher variation in blood lactate. Eventhough most of the studies consider colater effects the biggest problem of bad usage of NSAID`s by competitive athletes, the present study disagrees with the findings of Roi, 1994(9) indicating the possible ergogenic effect of Ibuprofen in well trained swimmers.